Outcomes of definitive radiotherapy vs. laryngectomy followed by adjuvant radiotherapy in patients with locally advanced laryngeal squamous cell carcinoma: real-world experience in a referral cancer center - Ali Kazemian; Ebrahim Esmati; Reza Ghalehtaki; Borna Farazmand; Nima Mousavi-Darzikolaee; Reyhaneh Bayani; Mahdieh Razmkhah; Maryam Taherioun; Niloufar Saeedi; Farrokh Heidari; Kaveh Zakeri (Radiation Oncology)
Abstract Background Laryngeal cancer is a common head and neck cancer. Surgical treatment can impair patients’ voice and swallowing function, making definitive radiotherapy a viable alternative for locally advanced cases. Methods To compare the outcomes of definitive versus adjuvant radiotherapy in patients with primary locally advanced laryngeal cancer, we retrospectively evaluated consecutive patients treated from 2007 to 2020. We assessed and compared the median and 3-year overall survival (OS), disease-free survival (DFS), distant metastasis control (DMC), and local recurrence-free survival (LRC) in all patients and in T4 patients exclusively. Results One hundred patients were studied, including definitive (N = 64) and adjuvant (N = 36) radiotherapy. The median follow-up was 29 months. Overall, the median OS in the definitive vs. adjuvant group was 100 months (95%CI = 46.5-153.5) vs. not reached, respectively (log-rank P = 0.506). The median DFS in the definitive vs. adjuvant group was 20 months (95%CI = 7.7–32.3) vs. not reached, respectively (log-rank P = 0.148). Three-year OS and DFS rates in all patients were 64% (95%CI: 48–78) vs. 75% (95%CI: 55–95) and 43% (95%CI:29–57) vs. 61% (95%CI: 41–81) in the definitive vs. adjuvant groups, respectively. Among T4 patients, the median OS in the definitive RT group vs. adjuvant group was not reached vs. 48 (95%CI = 0-105.3), respectively (log-rank P = 0.788). The median DFS in the definitive RT group vs. adjuvant group was 12 months (95%CI = 9.34–14.65) vs. 36 months (95%CI = 4.4–67.5), respectively (log-rank P = 0.868). Three-year OS and DFS rates were 71% (95%CI: 42–100) vs. 75% (95%CI: 50–100) and 40% (95%CI:21–79) vs. 56% (95%CI: 25–87) in the definitive vs. adjuvant groups, respectively. Conclusions Our analysis suggests that definitive radiotherapy in laryngeal cancer does not lead to a poorer outcome than total laryngectomy followed by adjuvant radiotherapy. In T4 patients, our findings should reassure clinicians and patients about the viability of definitive radiotherapy as a treatment approach.